Brexit decision puts strain on German economy - Ferdinand Fichtner; Christoph Große Steffen; Michael Hachula; Simon Junker; Simon Kirby; Claus Michelsen; Malte Rieth; Thore Schlaak; James Warren (DIW Economic Bulletin, 2016)
As a result of Britain's decision to leave the EU, global economic output is likely to grow at a somewhat slower pace than anticipated. The decision will have consequences for the UK and for the euro area in particular; this is also confirmed by simulations produced by the National Institute Global Econometric Model (NiGEM). An expected deterioration of economic relations-especially between the UK and the EU-and the associated increase in uncertainty have led to greater investment restraint. This has been accompanied by a devaluation of the British pound. Both will inhibit the development of the German economy with its strong focus on foreign trade. It will also dampen domestic investment and result in a lower level of consumption due to slightly weaker real wage growth. All in all, the German economy is likely to grow at a slower rate than previously predicted due to the Brexit decision. Growth is forecasted to be 0.1 percentage points lower in 2016 and 0.3 percentage points lower in 2017.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook; Brexit; European Integration